Selected autoimmune diseases as co-morbidities with hidradenitis suppurativa - narrative rewiew - Bednarczyk, Paulina; Chruścicki, Damian; Pelc, Marcin; Sitarek, Gracjan; Żerek, Marta; Płonka, Wojciech (Quality in Sport, 2024)
Introduction: Hidradenitis suppurativa (HS) is a chronic inflammatory skin condition marked by painful nodules and abscesses. It frequently coexists with autoimmune diseases, complicating management. Autoimmune conditions such as thyroid disorders, irritable bowel syndrome (IBS), systemic lupus erythematosus (SLE), and psoriasis are common in HS patients, necessitating a comprehensive care approach. Aim of the Study: This review evaluates the prevalence and impact of autoimmune diseases—autoimmune thyroid disorders, IBS, SLE, and psoriasis—on individuals with HS. Materials and Methods: A literature search of PubMed, Scopus, and Web of Science from 2018 to 2024 identified studies relevant to HS co-morbidities based on quality and relevance. Results: HS shows significant links with autoimmune thyroid disorders, IBS, SLE, and psoriasis. HS patients often have higher rates of hypothyroidism, hyperthyroidism, IBS, and SLE compared to the general population, suggesting shared inflammatory mechanisms. Conclusion: Recognizing co-morbid autoimmune diseases is vital for effective HS management. These associations emphasize the need for a multidisciplinary approach and further research to enhance understanding and treatment strategies.